Charles Wesley : a reader - Wesley, Charles, 1707-1788 (Oxford University Press, 2000)
This is an anthology of the writings of Charles Wesley. Best known for his hymns, such as 'Hark! the Herald Angels Sing', and 'Jesus, Lover of My Soul', Charles was the younger brother of John Wesley and the co-founder of Methodism. Despite his importance in the history of Protestantism, there is no collection of his writings in print, and indeed, little work has been done specifically on Charles in the last two generations. Tyson presents a chronologically arranged selection of the journals, sermons, letters, hymns, and poems in such a way as to both outline Wesley's life and illuminate the leading elements of his thought.